Unintentional diethylene glycol poisoning following the consumption of a shared alcoholic beverage - Hassen, Muhammed; Bhikoo, Raisa; Johannes, Clint; Chothia, Mogamat-Yazied (African Journal of Nephrology, 2018)
Diethylene glycol (DEG) is an uncommon cause of toxic alcohol poisoning. In the past, its ingestion in contaminated pharmaceutical products has resulted in mass outbreaks. We describe two isolated cases of unintentional DEG poisoning following the consumption of a shared alcoholic beverage and highlight the challenges that were confronted during the diagnostic work-up and management. Despite appropriate therapy, both cases had fatal outcomes, which emphasises the importance of early recognition of the condition and of instituting specific treatment.